Perceived Organizational Support and Employee Creativity: The Mediation Role of Calling. Issue 4 (1st October 2020) - Duan, Wenjie; Tang, Xiaoqing; Li, Yumei; Cheng, Xinfeng; Zhang, Hong
ABSTRACT: The current study identified one of the factors that contribute to employee creativity. In addition, it examined the relationship among perceived organizational support, calling, and employee creativity. A total of 410 employees from 68 organizations were included in the sample. The short version of the Survey of Perceived Organizational Support, Calling and Vocation Questionnaire, and Person–Environment Fit Scale for Creativity was administered. Results confirmed that perceived organizational support, calling, and employee creativity are positively and significantly correlated. Perceived organizational support and calling were relevant contributors to employee creativity. The mediating role of calling (i.e., the purposeful work dimension of calling) between perceived organizational support and employee creativity was discussed. These findings may explain how perceived organizational support can affect employee creativity. In addition, they may help unlock employee creativity via perceived organizational support and calling.